RANCANG BANGUN ALGORITMA DAN APLIKASINYA PADA AKUSTIK SINGLE BEAM UNTUK PENDETEKSIAN BAWAH AIR - Ma'mun, Asep; Manik, Henry M.; Hestirianoto, Totok (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Application of acoustic technology for underwater detection can be differentiated into four types, namely singlebeam, dualbeam, splitbeam and multibeam. The more acoustic beam constructed within the instrument, more expensive it gets and the higher details of detection and accuracy resulted. Thus, singlebeam acoustic remain as the most widely applied acoustics particularly in developing country. The presence of Cruzpro Fishfinder, as alternative multibeam. Acoustic instrument provide promixing as well as unfavoring consequences. Its capacity for internal data storage becomes handy, while unavailability for raw data signal processing requires important breakthrough. This study is developing algorithm for acoustic signal processing embedded in Matlab package. From this study obtain good accuracy and precision measurement to sphere ball. Several functions were applied, beam width, absorption coefficient and sound velocity; during development and sphere detection. Algorithm developed was proven efficient and useful for raw data processing of Cruzpro singlebeam acoustic, as revealed by low standard deviation of 0,13 with 95% confidence interval.